Clinical anesthesia - Barash, Paul G.; Cullen, Bruce F.; Stoelting, Robert K.; Cahalan, Michael K.; Stock, M. Christine; Ortega, Rafael A.; Sharar, Sam R.; Holt, Natalie F. (Books@Ovid., 2017)
Apply the latest know-how with a new chapter on cardiovascular pharmacology ... new coverage of autonomic pharmacology ... a greatly expanded Clinical Updates section ... updated coverage of occupational hazards ... and many other important additions. Focus on the most essential information with Key Points in every chapter. Advance your skills with 180 new Narrated Interactive Clinical Vignettes - which immerse you in a virtual classroom setting where a master teacher guides you through a focused discussion on common and uncommon clinical topics. A clinical question is posed, and you are given time to develop an appropriate answer. Then, in a stepwise fashion, you will see and hear the answer unfold. In addition to the Interactive vignettes, the ebook also comes with a collection of over 300 procedural videos to help hone your technique. -- Publisher.